Daily Shame and Hostile Irritability in Adolescent Girls with Borderline Personality Disorder Symptoms - Scott, Lori N. (Personal Disord, 2015)
Recent theoretical and empirical work suggests that adults with borderline personality disorder (BPD) have difficulty regulating both shame and anger, and that these emotions may be functionally related in clinically relevant ways (e.g., Schoenleber & Berenbaum, 2012b). The covariation of shame with anger-related emotions has important clinical implications for interventions targeting shame and uncontrolled anger in BPD. However, no studies have examined shame, anger, and their covariation in adolescents who may be at risk for developing BPD. Therefore, this study focuses on associations between BPD symptoms and patterns of covariation between daily experiences of shame and anger-related affects (i.e., hostile irritability) in a community sample of adolescent girls using ecological momentary assessment. Multilevel models revealed that girls with greater BPD symptoms who reported greater mean levels of shame across the week also tended to report more hostile irritability, even after controlling for guilt. Additionally, examination of within-person variability showed that girls with greater BPD symptoms reported more hostile irritability on occasions when they also reported greater concurrent shame, but this was only the case in girls of average socioeconomic status (i.e., those not receiving public assistance). Unlike shame, guilt was not associated with hostile irritability in girls with greater BPD symptoms. Results suggest that shame may be a key clinical target in the treatment of anger-related difficulties among adolescent girls with BPD symptoms.